Pembuatan Kontur Permukaan Piston Diameter 50 mm, Tinggi 15 mm AA 2618 Kapasitas 2 Buah/Jam - Ata Syifa’ Nugraha; Syamsul Hadi; Miftah Hijriawan; Feri Hidayatulloh; Syafria Wildan Hadi (Automotive Innovations Journal, 2026)
Lack of turbulence in mixing between air and fuel in the combustion chamber cylinder of a 100 cm3 4 stroke Otto engine is a problem faced. The purpose of making is to obtain a piston surface contour that produces optimal turbulence in mixing between air and fuel in the combustion chamber cylinder. The manufacturing method includes: piston surface contour design, experiments with several contour shapes on the impact of turbulence (trial and error) and data analysis, selection of piston material from AA2618 with a diameter of 50 mm and a height of 15 mm, comparison of power results from the results of various contour shapes from previous research, making a wavy contour from the inlet valve direction to the exhaust valve facing the hill height of 0.2 mm and a valley depth of 0.2 mm using CNC milling machining with a distance between hills of 3.5 mm, combustion trials in the cylinder with a comparison of power results between with and without a piston surface contour. The manufacturing results are in the form of a piston made of AA2618 material with a wavy contour surface measuring 0.2 m high and 0.2 mm valley from the inlet valve to the exhaust valve with a production cost of Rp. 100.000/unit, a production process duration of 30 minutes/unit which implies that the power of a 100 cm3 motor can increase by around 12%.